DEVELOPMENT DEVELOPMENT OF DIGITAL VISUAL INTERACTIVE LEARNING MEDIA FOR COLOR THEORY AND COMPOSITION - Yolandita Angga Reza; Wahyu Kurniawan; Okta Riyana Sari (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to improve the understanding of color theory and composition through the application of interactive digital visual-based learning media in the Color Theory and Composition course at the Graphic Design Study Program, Universitas Sains Indonesia. The research was motivated by the low level of student active involvement, difficulty in understanding abstract concepts of color theory, and learning that is still dominated by conventional methods that do not support visual exploration-based learning and Student Centered Learning (SCL). The study used the Classroom Action Research (CAR) method with the Outcome Based Education (OBE) and Student Centered Learning (SCL) approaches. The study was conducted in two cycles consisting of planning, action, observation, and reflection stages. Data collection techniques were carried out through observation of student activities, learning outcome tests, documentation, design project assessments, and student response questionnaires. The results showed that the use of interactive digital visual-based learning media was able to increase student activity from 64.37% in Cycle I to 88.12% in Cycle II. The completion of learning outcomes increased from 56.25% to 84.37%, visual creativity increased from 65.62% to 87.50%, and design analysis skills increased from 62.50% to 85.93%. The implementation of digital visual-based interactive media also improved students' abilities in analyzing color psychology, evaluating the use of color in visual communication, and creating design works based on color theory and composition. The results of the study showed that digital visual-based interactive learning media was effectively implemented in OBE and SCL-based graphic design learning to improve students' Higher Order Thinking Skills (HOTS) at levels C4 (Analyze), C5 (Evaluate), and C6 (Create).